Dampak Kebijakan Perubahan Kurikulum 2013 ke Kurikulum Merdeka - Amalina, Azkia (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: Indonesian education has regressed and fallen behind during the Covid-19 period, many children in Indonesia have problems with basics such as reading and arithmetic, which is why the government developed the Merdeka Curriculum as an important part of efforts to recover learning from the crisis that we have experienced for a long time. The purpose of this study is to examine how the independent curriculum policy has affected education in Indonesia, both positively and negatively. This research uses library research techniques (Library Research) The information used in this study comes from secondary sources including books, journals, articles, the web, and so on that have a relationship. Positive Impact of Implementing the Independent Curriculum: Creating a Positive Learning Space, Changing the Education System for the Better, Producing More Competent Teachers, Negative Impact of Implementing the Independent Curriculum: The abolition of UN began in 2021 and was replaced by the Minimum Competency Assessment and Character Survey (Askomi Suka), RPP designed into one sheet, Freedom to learn is considered not so mature in preparation.Keywords: Policy; Impact of Change; CurriculumAbstrak: Pendidikan Indonesia mengalami kemunduran dan ketertingalan selama masa Covid-19 banyak anak-anak di Indonesia yang bermasalah dengan dasae-dasar seperti membaca dan berhitung karena itulah pemerintah mengembangkan Kurikulum Merdeka sebagai bagian penting dalam uapaya memulihkan pembelajaran dari krisis yang sudah lama kita alami. Tujuan penelitian ini ialah untuk mengkaji bagaimana kebijakan kurikulum merdeka telah mempengaruhi pendidikan di Indonesia. Baik secara positif maupun negatif. Penelitian ini menggunakan teknik penelitian Library Research informasi yang digunakan dalam penelitian ini berasal dari sumber sekunder antara lain: buku, artikel, web dan sebagainya yang memiliki keterkaitan. Dampak positif dilaksanakannya kurikulum merdeka: menciptakan ruang pembelajaran yang positif, mengubah sistem pendidikan menjadi lebih baik, menghasilkakan guru yang lebih kompetem, dampak negatif dilaksanakannya kurikulum merdeka: penghapusan UN dimulai dari tahun 2021 dan diganti dengan Asesmen Kompetensi Minimum dan Survey Karakter (Askomi Suka), RPP dirancang menjadi satu lembar, kurikulum merdeka dinilai belum begitu matang dalam persiapan.Kata kunci: Kebijakan; Dampak Perubahan; Kurikulum